Al-Afghani dan Akar Pembaharuan Sosial-Teologi (Studi Kitab al-Radd ‘ala al-Dahriyyin) - Asrul Asrul (University of Darussalam Gontor, Indonesia, 2019)
This study provide an investigation about Jamaluddin al Afghani and his critique of materialism, an idea that push aside the spiritual values (religion). His thought attract more attention since he refuse the idea by the concept of faith to Allah and the judgement day. This concept normally used to strengthen Moslem’s theology. In the era of al Afghani, Moslems experienced a problem of Aqidah caused by the idea of Dahriyyun. Al-Afghani then write a book Risalah ar raddu ‘ala dahriyyin as a response to the problem, he provides the history, the form, the purpose, the negative effect of materialism also formulate the value of faith that can be applied. He deliver the concept of Arkan –Sittah, which has 2 main point, first tsalisah aqaid to lead a logic and second, salasah khisol to purify a soul, socialtheology concept aimed to awake Moslems from the risk of materialism.